2019
DOI: 10.1016/j.apenergy.2019.03.125
|View full text |Cite
|
Sign up to set email alerts
|

A solar combi-system utilizing stable supercooling of sodium acetate trihydrate for heat storage: Numerical performance investigation

Abstract: Highlights On-demand crystallization of sodium acetate trihydrate for heat storage  A numerical model was validated with data from system demonstration  Sensitivity analysis of solar collector area and heat storage volume  Annual solar fraction of 71% with 0.6 m 3 water and 1 m 3 of PCM for heat storage  1000 kWh of heat supplied by PCM units with 5.5 annual heat storage cycles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…A sensitivity analysis has been performed to assess the effect on the environmental impacts of changes in the life expectancy of the S-LHTES-PCM system (see Section 2.3). The S-LHTES-PCM system reaches a solar fraction of heat supply equal to 56% [19]. Since the total annual energy consumption of the house is 3723 kWh [11,19], this means 2085 kWh are provided by the S-LHTES-PCM system (41,700 kWh in 20 years).…”
Section: Inventory Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A sensitivity analysis has been performed to assess the effect on the environmental impacts of changes in the life expectancy of the S-LHTES-PCM system (see Section 2.3). The S-LHTES-PCM system reaches a solar fraction of heat supply equal to 56% [19]. Since the total annual energy consumption of the house is 3723 kWh [11,19], this means 2085 kWh are provided by the S-LHTES-PCM system (41,700 kWh in 20 years).…”
Section: Inventory Datamentioning
confidence: 99%
“…The S-LHTES-PCM system reaches a solar fraction of heat supply equal to 56% [19]. Since the total annual energy consumption of the house is 3723 kWh [11,19], this means 2085 kWh are provided by the S-LHTES-PCM system (41,700 kWh in 20 years). It is worth noting that the annual energy consumption of 3723 kWh is typical of a low-energy single-family house built according to the passive house standard located in a Danish climate (similar weather conditions as in the UK).…”
Section: Inventory Datamentioning
confidence: 99%
“…Contrary to the works presented in this sub-section, where the authors mostly focused on temperature responses and the increase in energy density in order to improve supply time, Englmair et al [ 59 ] mainly focused on reducing the energy consumption in buildings. They proposed a solar combi-system with short- and long-term heat storage with 22.4 m 2 evacuated tubular collectors, a 735 L water tank and four compact PCM units, each containing 150 L of SAT.…”
Section: Review Of Thermal Storages With Pcm In Building’s Hydronimentioning
confidence: 99%
“…The result is a thermal energy storage capacity that can be used on demand by the controlled initialization of crystallization. This storage concept has been demonstrated for a solar heating system [12,13] and showed potential for compact thermal energy storage systems in buildings [14]. Recently, Duquesne et al reported Xylitol [15] and Puupponen et al reported micro-structured polyol-polystyrene composites [16] as further promising materials with stable supercooling properties.…”
Section: Introductionmentioning
confidence: 99%